Reliability Analysis of Biomass Power Plant Using Loss of Load Probability Index at PT. Tanjung Buyu Perkasa Plantation - Muslimin, Muslimin; Larasati, Tantra Diwa; Tandiminanga, Agung (ELKHA : Jurnal Teknik Elektro, 2023)
The main function of a power generation system is to provide reliable electrical energy. This study aims to determine the reliability of Biomass Power Plants at PT. Tanjung Bayu Perkasa Plantation (PT. TBPP) in the years 2020, 2021, and 2022 using the Loss of Load Probability (LOLP) index calculation method. LOLP is a reliability index that indicates the possibility that the power plant cannot meet the demand. The LOLP of biomass power plants at PT. TBPP in 2020 amounted to 1.2769 days per year. However, the LOLP in 2020 does not comply with the standards set by the Republic of Indonesia Minister of Energy and Mineral Resources Decree in 2018. In contrast, in 2021, it was 0.53403 days per year, and in 2022, it was 0.41748 days per year, both of which meet the standards of the Republic of Indonesia Minister of Energy and Mineral Resources Decree in 2018. The LOLP is affected by the Forced Outage Rate (FOR) and demands exceeding the capacity. Based on the LOLP of biomass power plants at PT. TBPP in 2020, 2021, and 2022, it can be concluded that the reliability of biomass power plants at PT. TBPP is at a higher level of reliability compared to the micro-hydro power plant in Pantai Baru Pandasimo with a LOLP of 51.3627 days per year and the steam power plant at Pertamina EP Asset IV Field Sukowati with LOLP of 4.259535 days per year. The recommendation for future research is to explore ways better to optimize boiler operations in steam power plants at PT. TBPP.